Therapeutic strategies against bacterial biofilms - Bi, Yufang; Xia, Guixue; Shi, Chao; Wan, Jianglin; Liu, Longqiang; Chen, Yuan; Wu, Yueming; Zhang, Wenjing; Zhou, Min; He, Hongyan; Liu, Runhui (Fundamental research (Beijing), 2021)
The emergence of multi-drug resistance makes bacterial infection a major threat to public health and economy. The formation of bacterial biofilms is one of the main reasons of bacterial resistance. The complexity of chemical composition and physical structure makes the elimination of mature biofilms a difficult problem. The highly antibiotic resistant property of biofilms urgently calls for potent antimicrobial agents and novel antibiofilm strategies. Researchers have made a lot of efforts in this field. Here we review the current strategies to eliminate mature biofilms and progress in related drug delivery nanosystems, with the aim of inspiring researchers to design new antibiofilm systems. [Display omitted]